Kognition und Übersetzen. Über das Übersetzen von Konzepten - Kubaszczyk, Joanna (Glottodidactica, 1999)
In the article a new attempt has been made to define what is the unit of translation and how to distinguish it. In her considerations the author bases on the achievements of cognitive linguistics, claiming that the translator doesn’t translate words, phrases or texts but the content units which realises in the concepts of language. Thus, it becomes possible to distinguish the concepts as translation units a priori before actual taking up the translation. The training in distinguishing the concepts of language and analysing them becomes therefore an important element of translation.